Порівняльне фармакогностичне дослідження деяких видів роду Агастахе (Agastache J.Clayton ex Gronov) - Гуртовенко, І. О.; Гуртовенко, И. А.; Hurtovenko, I. O. (Запорізький державний медичний університет, 2020)
Дисертаційна робота присвячена фармакогностичному дослідженню агастахе фенхельного та агастахе кропиволистого, одержанню екстрактів на їх основі, розробці методів контролю якості на лікарську рослинну сировину та екстракти для створення нових лікарських засобів з гепатопротекторною, протизапальною та антимікробною активністю. Загалом у сировині A. foeniculum ідентифіковано 112 сполук, у сировині A.urticifolia − 112. Встановлено кількісний вміст флавоноїдів, гідроксикоричних кислот, катехінів, фенольних кислот, компонентного складу ефірних олій, вільних та зв’язаних цукрів та багатоатомних спиртів, жирних кислот, вільних та зв’язаних амінокислот, мінеральних елементів. Встановлено основні морфолого-анатомічні діагностичні ознаки сировини досліджуваних видів. Отримано сировину видів Agastache в культурі in vitro, визначено кількісний вміст основних груп БАР в отриманій сировині. Розроблено технології одержання ліпофільного та рідкого екстрактів з сировини агастахе фенхельного, розроблено технологічну схему комплексної переробки сировини; визначено основні БАР у отриманих субстанціях. Проведено стандартизацію сировини A. foeniculum і екстрактів та розроблено проекти МКЯ. Визначено гостру антимікробну, гепатотоксичну, антиоксидантну активність та гостру токсичність одержаних субстанцій. Диссертация посвящена фармакогностическому исследованию агастахе фенхельного и агастахе крапиволистого, получению экстрактов на их основе, разработке методов контроля качества на лекарственное растительное сырье и экстракты для создания новых лекарственных средств с гепатопротекторной, антиоксидантной и антимикробной активностью. Всего в сырье A. foeniculum идентифицировано 112 соединений, в сырье A.urticifolia − 112. Установлено количественное содержание флавоноидов, гидроксикоричных кислот, катехинов, фенольных кислот, компонентного состава эфирных масел, свободных и связанных сахаров и многоатомных спиртов, жирных кислот, свободных и связанных аминокислот, минеральных элементов. Установлены основные морфолого-анатомические диагностические признаки сырья исследуемых видов. Получено сырье видов Agastache в культуре in vitro, определено количественное содержание основных групп БАВ в полученном сырье. Разработаны технологии получения липофильного и жидкого экстрактов из растительного сырья агастахе фенхельного, разработана технологическая схема комплексной переработки сырья; определены основные БАВ в полученных субстанциях. Проведена стандартизация сырья A. foeniculum и экстрактов, разработаны проекты МКЯ. Определены антимикробная, гепатопротекторная, антиоксидантная активность и острая токсичность полученных субстанций. The thesis is devoted to pharmacognostic study of Agastache foeniculum (Pursch) Kuntze and Agastache urticifolia (Benth.) Kuntze, to the obtainment of the extracts from these species, development of quality control methods for herbal raw materials and extracts for the creation of new drugs with hepatoprotective, antiinflammatory and antimicrobial activity. Generally, 1. By means of chromatographic methods, 112 compounds were identified in the raw material of A. foeniculum, including 15 classes of BAS, among which polyhydric alcohols, mono- and disaccharides. In A.urticifolia raw materials, 113 compounds were identified, which include 15 classes of BAS, among which, for the first time, are hydroxycinnamic acids, flavonoids, polyhydric alcohols, mono- and disaccharides, organic and fatty acids, amino acids, mineral elements. For the first time, the qualitative composition and quantitative content of macro- and microelements of A. foeniculum and A. urticifolia herbs compared to the macro- and microelemental soil composition were investigated using X-ray fluorescence analysis. The fatty acids composition of A. foeniculum and A. urticifolia herbs was studied using GC-MS. The content of polysaccharides individual fractions in A. foeniculum and A. urticifolia herbs was determined first by gravimetric method. The content of mono- and disaccharides in A. foeniculum and A. urticifolia herbs was determined by gas-liquid chromatographу mass spectrometry. By means GC-MS defined the composition of volatile compounds in A. foeniculum and A. urticifolia herbs in ontogeny which introduced in Ukraine (Kyiv). It was revealed that the dominant components of the both studied species, regardless of the phase of ontogeny, are menthone, isomenthone, pullegon, D-limonene. In the process of ontogeny development the content of volatile compounds is changing, namely: the content of the pullegon is significantly increased in the mass flovering phase (2.8 times in A. foeniculum and in 2.64 times in A. urticifolia) as compared with the vegetative phase. By HPLC method in A. foeniculum herb was identified 16 amino acids, 7 flavonoids, 4 catechins, 5 hydroxycinnamic acids, 2 phenolic acids, 1 coumarin. It has been established that dominated by epigallocatechin (1411.7 mg/100 g), apigenin (1185 mg/100 g) and rosmarinic acid (1179.1 mg/100 g), somewhat less is content of rutin (633.1 mg/100 g), catechin (243.6 mg/100 g), chlorogenic acid (239.5 mg/100 g). For the first time, by spectrophotometry method the dynamics of accumulation of polyphenolic compounds in the raw materials of investigated species was studied. On the basis of the comparative analysis the optimal term for the procurement of raw materials A. foeniculum and A. urticifolia is phase of mass flovering. On the basic of macro- and microscopic study of raw materials A. foeniculum and A. urticifolia, basic morphological and anatomical signs and differences that can be used as key quality indicators in the standardization of the studied species and identification of the raw material are established. For the first time, it was received the culture of plants A. foeniculum and A. urticifolia, grown in vitro (from seed). A comparative study of the content of the main BAS in A. foeniculum and A. urticifolia herbs, which were cultivated in vitro and in open soil, and it was found that plants of both studied species successfully cultivated in aseptic culture of tissues (in vitro), accumulate significant biomass and differ in sufficiently high content of polyphenolic compounds, which is close to that of the corresponding plants when grown in open soil. According to the results of the study of BAS in the raw materials of investigated species, a scheme for the integrated processing of A. foeniculum raw material, which involves the sequential extraction of raw material with chloroform and obtaining a lipophilic extract, further extraction of the non-fatty raw material (shrot) with aqueous-alcoholic mixture and obtaining a polyphenolic extract. On the basis of the results of phytochemical, morphological and anatomical studies, the standardization of raw materials and extracts obtained were carried out for the first time, the drafts of quality-control technology of raw material «Agastache foeniculum herb», «Lipophilic Agastache foeniculum extract», «Polifenol Agastache foeniculum extract» were developed. Hepatoprotective activity of the A. foeniculum liquid extract has been studied. Based on the performed pharmacological studies, a more significant corrective effect of the A. foeniculum polyphenolic extract, as compared with the reference drug Silibor, has been shown on the liver function on the model of thiopental sleep in acute hepatitis. It has been established that the A. foeniculum extract exhibits antioxidant activity by its ability to suppress the auto-oxidation of adrenaline in vitro. The spectrum of antimicrobial activity of the A. foeniculum lipophilic extract was determined and this extract exhibited high antimicrobial activity against grampositive microorganisms: Staphylococcus aureus, Bacillus subtilis, moderate activity against gram-negative microorganisms: Pseudomonas aeruginosa, Escherichia coli, Proteus vulgaris and fungi Candida albicans.
Сравнительное фармакогностическое исследование некоторых видов рода Агастахе (Agastache J.Clayton ex Gronov)
Comparative pharmacognostic study of some species of the genus Agastache (Agastache J.Clayton ex Gronov)
Keywords: агастахе фенхельний; агастахе кропиволистий; трава; біологічно активні речовини; фармакогностичне дослідження; ліпофільний екстракт; поліфенольний екстракт; гепатопротекторна дія; антиоксидантна дія; антимікробна дія; агастахе фенхельный; агастахе крапиволистый; биологически активные вещества; фармакогностическое исследование; липофильный экстракт; полифенольный экстракт; гепатопротекторное действие; антиоксидантное действие; антимикробное действие; Agastache foeniculum; Agastache urticifolia; herb; biologically active substances; pharmacognostic research; lipophilic extract; polyphenolic extract; hepatoprotective effect; antioxidant activity; antimicrobial activity